Mechanical properties of composite sandwich structures with core or face sheet discontinuities. (1st March 2016) - Fotsing, E.R.; Leclerc, C.; Sola, M.; Ross, A.; Ruiz, Edu
Abstract: A combination of tensile tests, three-point bending tests, compressive tests, and low velocity impact tests was used to analyze the influence of face sheet modification and core discontinuities of composite sandwich panels. These modifications are the results of the effort to add new functionalities such as damping and/or to ease assembly of composite sandwich panels. This experimental analysis revealed that the tensile and flexural properties of sandwich structures remain unaltered when discontinuities of 2 mm are introduced in the core or small viscoelastic patches are inserted between face sheet plies. However, compressive properties are significantly reduced by the presence of such core or skin modifications. Finally, the energy absorbed during low velocity impact increases with increase interleaved viscoelastic film and increasing core discontinuity. Thus a special care must be taken at the early design stage to protect such vulnerable areas.